Evaluation of bismuth shielding in reducing thyroid radiation dose during neck multidetector computed tomography examinations: a comparative study - Başar, Yeliz (The European Research Journal, 2025)
Objectives: This study pointed to assess the viability of bismuth protecting in lessening thyroid radiation measurements amid neck multidetector computed tomography (MDCT) examinations and to explore alternative protecting strategies which will moderate negative impacts on picture quality. Methods: The study involved 20 patients undergoing neck MDCT. Thermoluminescent dosimeters (TLDs) were utilized to degree radiation measurements to the thyroid organ with and without bismuth protecting. Measurable investigations, counting combined tests t-test and Wilcoxon signed-rank test, were conducted to evaluate the importance of dosage decrease. Results: Bismuth protecting altogether diminished the radiation measurements to the thyroid organ by 43.95%, from 24.50 mGy to 17.59 mGy (P<0.01). The reduction was statistically significant in women (P<0.01) but not in men (P>0.05) due to the small sample size. No significant correlation was found between age and radiation dose levels (P>0.05). Conclusions: Bismuth shielding effectively reduces thyroid radiation dose during neck MDCT examinations. However, the potential increase in image noise necessitates careful management to maintain diagnostic accuracy. Further research is needed to optimize shielding techniques and explore alternative methods to minimize radiation exposure while preserving image quality.